Economic value of portfolio diversification: Evidence from international multi-asset portfolios - Prateek SHARMA (Theoretical and Applied Economics, 2017)

(untitled)
We examine alternative approaches of measuring portfolio diversification, and test the empirical relation between diversification and the future risk-adjusted performance in a crosssection of international multi-asset portfolios. We use the Woerheide and Persson measure as a weight-based diversification measure, the conditional diversification measure as a risk-based diversification measure, and the effective number of bets (ENB) as a factor based diversification measure. We find that only the ENB measure is a significant predictor of the future Sharpe ratios. The economic gains of diversification, as measured by the ENB measure, are large and robust to the investor’s risk aversion and investment horizon.